The Powers of the President against the Legislative Branch; According to the Constitution of Afghanistan - Jalili, Abdul Mateen; Faizy, Sawab Gul; Shenwari, Zahidullah (Integrated Journal for Research in Arts and Humanities, 2022)
According to the Afghan Constitution, the President is the head of state and three branches, and also the head of the executive branch. The Constitution of Afghanistan in generally defines the powers of the President, one of which is the powers of the President against the legislative branch. Since these powers are not clearly defined in the constitution. Therefore, the constitution of Afghanistan needs a clear and light interpretation, which is a major problem in the Afghan constitution. The constitution also gives the president more powers than responsibilities, the main reason is that when the constitution was drafted; in addition to external interference, at the time the President of Afghanistan, Hamid Karzai, placed more powers in the constitution for his own benefit. So, it can be said the president had not exercised his powers against the legislative branch in accordance with the constitution.